Asesmen Pembelajaran dengan Tools Generative AI untuk Guru pada Pendidikan Vokasi - Mangoki, Willson; Krismiyati; Yulia, Hanita (Jurnal Pengabdian KOLABORATIF, 2026)
The rapid advancement of generative artificial intelligence (generative AI) has created new opportunities for innovation in assessment practices within vocational education. Nevertheless, a large proportion of vocational high school (SMK) teachers continue to experience difficulties in understanding, contextualizing, and ethically integrating this technology into the design of assessments that are aligned with the demands of 21st-century skills. As a result, the evaluations implemented in classrooms tend to remain conventional and insufficiently representative of authentic workplace conditions in industry. This community engagement program was designed to enhance the competencies of SMK teachers in developing AI-based assessments that are adaptive, contextual, and responsible. The training was conducted using a hybrid approach, encompassing conceptual seminars, interactive discussions, and hands-on practical sessions utilizing MagicSchool as an AI platform for assessment design. A total of 100 teachers participated in the program, consisting of 30 onsite participants and 70 online participants. Evaluation results indicate an increase in the average score from 84.0 to 94.0, demonstrating a significant improvement in teachers’ assessment design competencies. Overall, the program proved effective in strengthening teachers’ technological literacy and pedagogical capacity, while also promoting the ethical and contextually relevant application of AI in industry-oriented vocational learning.